Understanding the molar volume of alkali-alkaline earth-silicate glasses via Voronoi polyhedra analysis. (June 2019) - Yang, Yongjian; Tokunaga, Hirofumi; Ono, Madoka; Hayashi, Kazutaka; Mauro, John C.
Abstract: We show that the molar volume of an alkali-alkaline earth-silicate glass system can be well understood through Voronoi polyhedra. A good agreement of the partial molar volumes of Na2 O, K2 O, MgO, CaO, and SiO2 is achieved between molecular dynamics simulations using Voronoi analysis and experimental data. The physical meaning of the partial molar volume is illustrated considering the Voronoi volume contributions of both cations and oxygen atoms. Discrepancies between the linear model predictions and the measurements observed in both molecular simulations and experiments can be attributed to the Voronoi volume change of potassium due to its complex interaction with other species. Graphical abstract: Unlabelled Image